If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12h - 18 = (4h - 6)
We simplify the equation to the form, which is simple to understand
12h-18=(4h-6)
Remove unnecessary parentheses
12h-18=4h-6
We move all terms containing h to the left and all other terms to the right.
+12h-4h=-6+18
We simplify left and right side of the equation.
+8h=+12
We divide both sides of the equation by 8 to get h.
h=1.5
| 12x-60=0 | | 6(4y-1)=5 | | 2(x+5)=8 | | 3-n=33 | | x-6=(x-4)1/2 | | y=1.5(1) | | V=dt | | 4x^2-8=20 | | 0=1.5x | | 10(-10x+1)= | | 9n^2-50n-80=0 | | -2a+3(4-a)=-3(a+4)-6 | | V=IxR | | 0.4x^3+0.6x^3-0.3x^3= | | x^2+x+20=0 | | -4m=-32 | | x-7=-20 | | 4x-7x(5x-8)=x-8 | | y=-2(1) | | -4(2z+5)=4 | | 5x+9=11+4x | | j-17=2j+13 | | 5x=3x-18 | | n-3n=14-4 | | d-4d=d+1-4d | | .2x-y=2 | | -18y=9 | | 4x^2y-16xy^2= | | .2-y=2 | | 6(z-1)-5(z+1)=8(z+1) | | (z^4-4)(z^4-9)= | | q-43.94=400.12 |